PENGARUH PERENCANAAN PAJAK, PENGHINDARAN PAJAK, DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Sektor Keuangan yang Terdaftar di Bursa Efek Indonesia 2020-2022) - Ichfa Aulia Yahya; Herry Laksito (Diponegoro Journal of Accounting, 2025)
This study aims to examine the factors that affect earnings management in the financial sector listed on the Indonesia Stock Exchange (IDX) in 2020-2022. The independent variables used in this study are tax planning, tax avoidance, and deferred tax liabilities. While the dependent variable used is earnings management. The population of this study uses secondary data obtained from financial statements of companies listed on the Indonesia Stock Exchange (IDX). The method used was purposive sampling method and 158 data were obtained from financial sector companies listed on the Indonesia Stock Exchange (IDX) in 2020- 2022. Multiple linear regression analysis was used in this study to analyze the data. The results showed that tax planning has no significant effect on earnings management. Tax avoidance has no significant effect on earnings management. And deferred tax expense has a significant effect on earnings management.